Italo Calvino and the Spanish language: Between Latin America and Spain - Ciotti, Monica (Cuadernos de Filología Italiana, 2021)
This paper analyses the editorial history of Italo Calvino’s works that are translated, and subsequently published, in Spanish. In particular, the research investigates the reasons for the delay of the meeting between the Spanish public and the Calvinian opera, by starting from the discovery of the Argentine debut. In addition, an analysis in conduct to explore linguistic, cultural, and editorial diversities. Lastly, wherever possible, the Spanish paratexts are studied to determine how the first encounter between Calvino’s work and the reader takes place outside the national scene.
Keywords: Italo Calvino; translation; publisher; Argentina; Spain